Diferenciální rovnice systémů s úzkými místy - Šimečková, Kateřina (Vysoké učení technické v Brně. Fakulta strojního inženýrství, 2016)
Tato bakalářská práce se zabývá analýzou diferenciálních rovnic popisujících systémy s úzkými místy. Studovaný model soustavy je odvozen na základě hydrodynamické analogie. Dále jsou odvozeny podmínky a algoritmy popisující udržitelnost systému, tedy stav, kdy fronta v žádném úzkém místě nepřesáhne dovolenou úroveň. Vše je doplněno ilustrativními příklady.

The thesis deals with an analysis of differential equations for systems involving bottlenecks. The employed mathematical model originates from a hydrodynamical analogy. Further, the notion of sustainability, i.e. a situation when queues in bottlenecks do not exceed allowed limits, is discussed. In particular, conditions and algorithms enabling to describe sustainability properties of a given system are provided. The results are illustrated on several examples.
Differential equations for systems involving bottlenecks
Keywords: úzká místa; diferenciální rovnice; hydrodynamický model; bottlenecks; differential equations; hydrodynamical model